Study of carbon dioxide capture through adsorption - Soo, Kok Chuan. (2013)
As a matter of fact, there is more and more carbon dioxide being released into atmosphere nowadays and a methodology is needed to reduce the amount of carbon dioxide for cleaner energy. Therefore, a study of physical gas adsorption of carbon dioxide with activated carbon (Maxsorb-III) and zeolite was carried out to measure experimentally the amount of CO2 uptakes and these data are fitted with different isotherms models. The adsorption efficiency of both materials are compared.